1823 The in-between teens: a new pathway for 16 and 17 year old inpatients at Darent Valley hospital. (15th December 2022) - Lam, Sophie; O'Connor, Laura; Brooks, Lynn; Bell, Emily; Gupta, Alok
Abstract : Objectives: Darent Valley Hospital is a DGH in Kent. The Paediatric Adolescent/Transition Specialist Nurse role was introduced in February 2021. The Specialist Nurse and Paediatric Adolescent Consultant started working together in May 2021. The aim was to work in collaboration with the paediatric and adult services to bridge the gap between them. It soon became apparent that management of 16 and 17 year inpatients was the most pressing need. We set out to capture the voice of the young person on their journey from the ED to the ward. Until 2021, all 16 and 17 year olds requiring admission, were admitted to adult wards under the care of adult teams; unless they were already known to paediatric teams and had not yet been fully transitioned. Adult wards had identified that they felt ill equipped to meet the needs of these young people. Methods: We set out to capture qualitative and quantitative data about this group. Inpatients aged 16 and 17, together with their parents if available, were interviewed face-to-face and/or completed a written questionnaire. Complaints and datixes were reviewed. Monthly data was analysed and a deep dive into every inpatient for May 2022 was conducted. Results: The interviews, questionnaires, complaints and datixes were analysed to look for common themes which have been captured in the form of a word cloud (Image 1). Image 1 The voice of the young person Data was gathered on inpatient admissions over a seven month period (November 2021-May 2022) to calculate the average number of 16 and 17 year olds in the hospital per night (table 1). A deep dive was performed to review the admissions May 2022 (table 2). The list of inpatients provided by business information was crosschecked reviewing discharge notifications and electronic notes. Conclusions: Whilst numerically a small proportion of inpatients (mean 1.7 per night), these young people are a challenge to manage well. They are legally classified as children yet historically have been treated as adults, expected to stay in wards with much older patients, often designed with the needs of the elderly and frail in mind, whilst separated from their families and support networks. A new inpatient pathway (Image 2) has been designed by the adolescent team with input from ED, adult medical and surgical matrons, safeguarding, mental health and learning disability teams. All young people aged 16 and 17 are to be given the option of whether they would prefer admission on a paediatric or adult ward. There is a new assumption that most young people would be better served on a paediatric ward. Where an adult ward is selected (or required due to bed pressures) then a sideroom is used to ensure patient safeguarding, with parents/carers allowed unrestricted visiting and the option to stay overnight. In future we aim to develop an adolescent unit for 13–17 year olds, co-located with paediatrics.